Cyberbullying di Media Sosial dalam Prespektif Kriminologis dan Viktmologis - Al Idrus, Nur Fadilah; Widowati, Yeni (UNIVERSITAS ISLAM KADIRI, 2022)
ABSTRACT Cyber​​bullying is the impact of the development of technology that triggers an increase in internet use. The author discusses the study of criminology and victimology of cyber bullying on social media with the formulation of the problem: 1. How is cyber bullying by adolescents on social media analyzed from criminological theory?. 2. How are victims of cyber bullying on social media assessed from victimology theory? This research is a normative research. Conclusions: 1. Cyber ​​bullying cases to Betrand. The perpetrator is a teenager, the criminological analysis of the perpetrator in this case uses social control theory and differential association theory. Social control theory: a. Affection, b. Commitment, c. trust. 2. Victimology analysis has now revealed a theory of victimization without blaming the victim, of course it is very far from the previous victimology theory, especially the positive victimology theory which tends to be victim blaming. According to the author, what can be related to cyber bullying cases on social media is the modern lifestyle exposure theory victimology and daily routine theory. guilty or ideal victim, Victim with little fault and victim with stupidity, Based on psychological, biological, and social factors cyber bullying can be associated with the acquisitive or the wanton. In dealing with cyber bullying cases in the future, the author will associate it with critical victimology theory. Keywords: Cyber Bullying, Criminology, Victimology. ABSTRAK Cyber bullying merupakan dampak dari bekembangnya teknologi sehingga memicu peningkatan penggunaan internet. Penulis membahas mengenai kajian kriminologi dan victimologi cyber bullying di media sosial dengan rumusan masalah: 1.Bagaimana cyber bullying oleh remaja di media sosial dianalisis dari teori kriminologi?. 2.Bagaimana korban cyber bullying di media sosial dikaji dari teori victimologi?. Penelitian ini merupakan penelitian normatif, Kesimpulan: 1. Kasus cyber bullying kepada Betrand. Pelakunya seorang remaja, analisis kriminologi pelaku pada kasus ini menggunakan teori kontrol sosial dan teori asosiasi diferensial. Teori kontol sosial: a. Kasih sayang, b. Komitmen, c. Kepercayaan. 2. Analisis victimologi kini telah menampakkan suatu teori viktimisasi tanpa harus menyalahkan korban, tentu sangat jauh dari teori victimologi terdahulu utamanya teori victimologi positive yang cenderung bersifat victim blaming. Menurut penulis yang dapat dikaitkan dengan cyber bullying kasus di media sosial ialah teori victimologi modern lifestyle exposure and daily routine theory, sebab-sebab yang menjadikan korban sebagai korban dalam kejahatan, korban cyber bullying mereka tergolong participating victims, juga dalam kategori korban yang sama sekali tidak bersalah atau korban ideal, Korban dengan sedikit kesalahan dan korban dengan kebodohannya, Berdasarkan faktor psikologis, biologis, dan sosial cyber bullying dapat dikaitkan dengan the acquisitive ataupun the wanton. Dalam menangani kasus cyber bullying kedepannya penulis kaitkan dengan teori viktimologi kritis. Kata kunci: Cyber bullying, Kriminologi, Viktimologi.